A Rare Case of Primary Pulmonary Amoebiasis without Gastrointestinal Involvement: A Case Report - Arie Gradiyanto Nugroho; Edijono Edijono (Jurnal Respirasi, 2021)
Introduction: The main pathogen of amoebiasis is Entamoeba histolytica which is very common in tropical and developing countries, where sanitation, hygiene, and low socio-economic status are major problems. The most common site of infection is the intestinal mucosa. For extraintestinal amoebiasis, the most common sites are the liver, followed by the lungs and brain.Case: A 15-year-old male was presented to the ER with chief complaint of breathlessness for the last 10 days, accompanied by productive coughing with dark brown sputum and pain on lower right chest. The patient had fever while the disease progressed. Gastrointestinal symptoms were denied. Physical examination showed lowered breathing sound on the right lung, dullness on lower right chest, and usage of accessory breathing muscles. USG found heteroechoic lesion of 8x7cm in size suspicious of lung abscess, later on confirmed as Entamoeba histolytica found in sputum sample, while abdominal USG showed no abnormality. The patient was admitted for antibiotic therapy and consultation to cardiothoracic surgeon.Discussion: One of the rarest routes of amoebiasis is primary deposition of cysts to the lungs through aspiration. Pulmonary amoebiasis often causes abscess formation, produces brown-colored sputum called “anchovy sauce”. It is notable that we found one of the rarest cases of amoebiasis infection, where there is a pulmonary infection without any intestinal involvement.Conclusion: Whilst infection of primary pulmonary amoebiasis is very rare, it is still an important etiology to put on the differential diagnosis of pulmonary abscess. Therefore, sputum examination or biopsy is required even when there are no gastrointestinal disturbances.